Supervisory turnover in outpatient substance abuse treatment. - Knight DK; Broome KM; Edwards JR; Flynn PM; Knight, Danica K; Broome, Kirk M; Edwards, Jennifer R; Flynn, Patrick M (Journal of Behavioral Health Services & Research, 2011)
Staff turnover is a significant issue within substance abuse treatment, with implications for service delivery and organizational health. This study examined factors associated with turnover among supervisors in outpatient substance abuse treatment. Turnover was conceptualized as being an individual response to organizational-level influences, and predictors represent aggregate program measures. Participants included 532 staff (including 467 counselors and 65 clinical/program directors) from 90 programs in four regions of the USA. Using logistic regression, analyses of structural factors indicated that programs affiliated with a parent organization and those providing more counseling hours to clients had higher turnover rates. When measures of job attitudes were included, only parent affiliation and collective appraisal of satisfaction were related to turnover. Subsequent analyses identified a trend toward increased supervisory turnover when satisfaction was low following the departure of a previous supervisor. These findings suggest that organizational-level factors can be influential in supervisory turnover.